3D intense beam dynamics simulation by using moments method - Kazarinov, N.; Aleksandrov, V.; Shevtsov, V. (Вопросы атомной науки и техники, 2008)
The program for 3D simulation of the intense charge particle beam dynamics on the base of the Multi-Component Ion Beam code is described. Fast analysis and study of the averaged beam characteristicsis performed by the moments method.